2021
DOI: 10.1177/0363546521992359
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Clinical Improvement and the Disappearance of Calcifications After Ultrasound-Guided Percutaneous Lavage of Rotator Cuff Calcific Tendinopathy: A Post Hoc Analysis of a Randomized Controlled Trial

Abstract: Background: Calcific tendinitis of the rotator cuff is a frequent cause of shoulder pain. Ultrasound-guided percutaneous lavage (UGPL) is an effective treatment, but factors associated with good clinical and radiological outcomes still need to be identified. Purpose: To study the clinical, procedural, and radiological characteristics associated with improved shoulder function and the disappearance of calcification on radiograph after UGPL. Study Design: Case-control study; Level of evidence, 3. Methods: This i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Finally, steroid injections may be recommended when the calcification has become poorly defined on imaging and it is no longer possible to puncture it. The disappearance of the calcification between 3 and 12 months is also observed in one-third of patients, without any additional treatment [38].…”
Section: Chronic Stagementioning
confidence: 73%
“…Finally, steroid injections may be recommended when the calcification has become poorly defined on imaging and it is no longer possible to puncture it. The disappearance of the calcification between 3 and 12 months is also observed in one-third of patients, without any additional treatment [38].…”
Section: Chronic Stagementioning
confidence: 73%
“…CR was assessed in nine studies,153 157 175–180 183 US in five179–183 and MRI in a single study 178. Study design included one SLR without meta-analysis, whose references were reviewed,176 two RCTs153 179 and eight cohort studies 157 175 177 178 180–183. Treatment included injections, aspiration, needling, lavage, extracorporeal shockwave therapy and radiotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…The results across studies were variable, with some suggesting that the morphology and size of the calcifications on CR and US could predict response to treatment,157 177 180–182 184 while others yielded negative results 153 175 178 179 183. One study on US and one on MRI investigating inflammatory changes suggested a predictive role,178 181 while two US studies did not 179 182. A single study reported a predictive role of acromial shape on CR 175…”
Section: Resultsmentioning
confidence: 99%
“…The necessity of removing the intraosseous deposit in the surgical treatment of calcific tendinitis is still under debate [12, 13, 22, 23, 27]. Although the results in the previous series were generally successful, they show a range of satisfaction rates.…”
Section: Discussionmentioning
confidence: 99%